2013
DOI: 10.1177/1098612x13479114
|View full text |Cite
|
Sign up to set email alerts
|

Induction of scratching behaviour in cats: efficacy of synthetic feline interdigital semiochemical

Abstract: The aim of the study was to evaluate the effects of synthetic feline interdigital semiochemical (FIS) on the induction of scratching behaviour in cats during a standardised behavioural test. The trial was a randomised blinded study on a single group of subjects, following a crossover design. The scratching behaviour of 19 cats was evaluated during a standardised test in which cats were introduced to an area with one scratching post. Each cat acted as its own control (receiving, at random, FIS then placebo or v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 33 publications
1
19
0
1
Order By: Relevance
“…51 Alternatives to declawing include regular nail trimming and use of artificial nail caps to minimize property damage and provision of appropriate scratching surfaces such as scratching posts and substrates. 52 A study 53 of 128 Italian cat owners found that sexually intact male cats were more likely to scratch other surfaces when a scratching post was absent from the environment, and Cozzi et al 39 reported that a feline interdigital semiochemical, a cat pheromone replacement made of fatty acids, can be used to control excess behavioral scratching through placement of this substance on a desired scratching location. Behavior modification methods may also decrease environmental scratching.…”
Section: Declawingmentioning
confidence: 98%
See 1 more Smart Citation
“…51 Alternatives to declawing include regular nail trimming and use of artificial nail caps to minimize property damage and provision of appropriate scratching surfaces such as scratching posts and substrates. 52 A study 53 of 128 Italian cat owners found that sexually intact male cats were more likely to scratch other surfaces when a scratching post was absent from the environment, and Cozzi et al 39 reported that a feline interdigital semiochemical, a cat pheromone replacement made of fatty acids, can be used to control excess behavioral scratching through placement of this substance on a desired scratching location. Behavior modification methods may also decrease environmental scratching.…”
Section: Declawingmentioning
confidence: 98%
“…39 Farm cats have been reported to scratch between 1 and 6 times a day. Scratching behavior is driven almost entirely by the presence of conspecifics 39 but is still present in cats housed singly in homes.…”
Section: Declawingmentioning
confidence: 99%
“…In a crossover clinical trial of 19 laboratoryhoused cats, the synthetic analogue of FIS was shown to modify the latency, duration and frequency of scratching behaviors compared with placebo. 16 In an in-home test performed in more than 150 feline households by Ceva, the product was effective in redirecting the cats' scratching onto their scratching post, while preventing or reducing unwanted scratching of furniture. 17,18 Discourage the use of inappropriate substrates Owners may resort to a variety of methods to discourage the cat from performing undesirable scratching behaviors.…”
Section: Jfms Clinical Practice 239mentioning
confidence: 99%
“…One study showed that scratching posts with feline interdigital semiochemical (FIS) were scratched for longer and more frequently by cats than posts without FIS. 7 As punishment does not seem to effectively reduce inappropriate scratching, 5 an alternative, more ethical, option is to redirect the behavior to a designated scratcher that is preferred and/or appealing to cats. For the prevention or reduction of scratching inappropriate items in adult cats, it is of great importance to train them to use scratchers at a young age.The current study compared in kittens (<2 months old) any preference for different types/styles of scratchers and evaluated the effectiveness of catnip and odor from another cat in inducing scratching behavior.…”
Section: Introductionmentioning
confidence: 99%